(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: i) To determine the frequency of Caesarean section. ii) To analyze the indications of Caesarean section. iii) To determine complications of Caesarean section in both emergency and elective group. Methodology: A descriptive study was carried out in Sir Ganga Ram Hospital, Lahore which is 550 bedded tertiary care hospital. The study was carried out from Jan. 2001 to Dec. 2001. All patients undergoing lower segment Caesarean section during this period were included in study. It was including all booked and unbooked patients admitted for Caesarean section for any indication. Factors analyzed were age, parity, intra and postoperative complications. Patients having classical Caesarean section and hysterotomies were not included in the study. Data was analyzed using frequency and percentage. Results: During one year period 903 patients underwent for Caesarean section. The rate of Caesarean section was 23.15%, with 21.9% elective and 78.07% emergency operations, 589 (65.22%) patients were admitted through emergency and remaining through out patient department. Most common indication was failure of progress 138 (15.2%), foetal distress 119 (13.17%) and contracted pelvis 102(11.2%) in emergency Caesarean section group. Elective Caesarean section group previous Caesarean section 66(7.3%), breech presentation 47 (5.20%) and antepartum haemorrhage 25(2.76%). Most common intra-operative complications were post partum haemorrhage, those related to anaesthesia, tears and lacerations. All these complications were more common in emergency group than elective Caesarean section. Post operative complications were anaemia post partum haemorrhage, gastrointestinal tract problems including paralytic ileus and wound infection. There were total 3 (0.33%) deaths, all occurring in emergency Caesarean section. Conclusion: Majority of the patients underwent for emergency Caesarean section and most complications occurred in cases of emergency Caesarean section group.